Chronic prostatitis/chronic pelvic pain syndrome increases susceptibility to seizures in rats and alters brain levels of IL-1β and IL-6 - Šutulović, Nikola; Grubač, Željko; Šuvakov, Sonja; Jovanović, Đurđa; Puškaš, Nela; Macut, Đuro; Marković, Aleksandra Rašić; Simić, Tatjana; Stanojlović, Olivera; Hrnčić, Dragan (Epilepsy research, 2019)
Summary Paragraph: Rats with experimentally induced chronic prostatitis/chronic pelvic pain syndrome are more prone to seizure induction. Increased levels of IL-1β and IL-6 were determined in the thalamus and cortex of CP/CPPS animals. IL-1β and IL-6 brain levels may potentially mediate this increased seizure susceptibility. [Display omitted] •CP/CPPS rats are more prone to seizure induction.•Increased levels of IL-1β and IL-6 were determined in the thalamus and cortex of CP/CPPS animals.•CP/CPPS induced brain hyperexcitability is associated with increased levels of IL-1β and IL-6. Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS) is a result of interplay between psychological, immune, neurological and genetic factors, manifested by variety of urological, as well as brain-related symptoms. However, its relation with brain excitability has not been addressed. herefore, our aim was to assess susceptibility to seizures in rats with CP/CPPS. We induced CP/CPPS in adult rats by intraprostatic injection of 3% λ-carrageenan. Sham operated rats served as controls (0.9% NaCl, Sham). On day 7 upon injection, rats were treated with lindane (4 mg/kg) and observed for convulsive behavior (seizure incidence, latency and severity) and EEG manifestations (number and duration of ictal periods). Interleukin levels (IL-1β and IL-6) were measured in prostate, hippocampus, thalamus and cerebral cortex. Scrotal skin mechanical pain thresholds were determined and prostates were histologically evaluated. Animals with CP/CPPS showed significantly higher incidence, decreased latency time and augmented severity of lindane-induced seizures compared with Sham group. EEG revealed increased number of ictal periods in CP/CPPS rats. Higher levels of IL-1β and IL-6 were determined in the thalamus and cortex in CP/CPPS animals vs. Sham. IL-1β level was higher and IL-6 was lower in prostates from CP/CPPS animals comparing to Sham. CP/CPPS development was verified by histological findings of nonbacterial inflammation in the prostates, as well as by significantly decreased scrotal pain threshold in CP/CPPS animals. On the basis of this research, we concluded that CP/CPPS increases susceptibility to lindane-induced seizures in rats associated with increased level of IL-1β and IL-6 in the cortex and thalamus.